Comportamentos de impulsividade, autoagressão e ideação suicida entre adolescentes escolares. - Quixadá Fontenele, Thaisa; Mazza Nunes Aragão, Joyce; Menezes Sousa, Paulo Regis; da Cunha Gomes, José Augusto; Nazaré de Oliveira, Eliany; Osawa Vasconcelos, Maristela Inês; do Amaral Gubert, Fabiane (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2024)
Objective: To verify the profile of impulsive behavior, self-harm, and suicidal ideation among adolescent schoolchildren in a city in the interior of Ceará, Brazil. Method: This is a cross-sectional study conducted in an elementary school in the interior of Ceará, with 245 adolescents aged between 13 and 16. Data was collected in the second semester of 2022 using the Impulsivity, Self-harm, and Suicidal Ideation Questionnaire (QIAIS-A). A descriptive analysis was conducted using the statistical programming software R version 4.1.2. Results: Most participants, 126 (51.43%), were female, self-described as brown race/color, 170 (69.39%). Regarding sexual orientation, 197 (80.41%) students declared themselves heterosexual. 164 (66.94%) adolescents lived with their father and mother and/or siblings. Among the participants, 213 (86.93%) stated that they had already had some act related to impulsivity, 109 (44.49%) had already had some self-harm behavior, and 155 (63.26%) participants had already expressed suicidal ideation. Conclusion: The results obtained reveal high numbers related to impulsivity, self-harm, and suicidal ideation in this population, which reaffirms the importance of mental health promotion, and prevention actions aimed at the public.